Learning teamworking and non-technical skills: a pilot study of a postgraduate course at the University of Florence - Veronica Verde; Yari Bardacci; Lorenzo Ballerini; Samuele Baldassini Rodriguez; Chiara Balestri; Paolo Iovino; Simone Belli; Stefano Bambi (Infermieristica Journal, 2023)
Abstract Background: Non-technical skills (NTS) are the cognitive and social skills that integrate the technical skills of a worker. In healthcare systems, NTS exert positive effects on patients’ safety and healthcare professionals’ efficiency. Aim: This study aims to assess the degree of NTS knowledge, before and after a workshop administered to a group of 17 nursing students attending a critical care nursing postgraduate course at the University of Florence. Methods: A cross-over design study was conducted. The workshop was composed of short lectures on “fundamentals of teamworking” and “team building and communication”, followed by team activities and gaming. At the end of the day a medical “escape room” about a shock scenario, was developed and run by the students. A questionnaire investigating participants’ entertainment and self-evaluation of NTS use, was administered at the end of the simulation sessions. Results: A sample of 17 nurses was enrolled. Pre-posttests were completed by 16 participants. Seventy-five % (n=12) of the respondents found the team working activities exciting. Most of the participants (62.5%, n=10) considered the “escape shock room game” enjoyable and stimulating and would recommend the learning activities to other healthcare professionals (75%, n=12). Compared to pre-test scores, statistically, significant improvements in NTS understanding were found on the topics of “team building” (p<0.001; r= -0.60), “teamworking” (p= 0.001; r= -0.56), “membership” (p= 0.001; r= -0.56), “hard skills” (p= 0.001; r= -0.57), “soft skills” (p=0.001; r= -0.56) and “situational awareness” (p< 0.001; r= -0.61) items. Conclusions: The process of NTS training is well accepted by critical care nursing students and can improve their competencies. Therefore, simulation based NTS training programs and gaming activities should be periodically implemented as part of Critical Care Nursing Postgraduate Courses.